2017
DOI: 10.1159/000480154
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Evaluation Comparing the Performance of a Novel 19-G Flexible Needle to a Commercially Available 22-G EBUS-TBNA Sampling Needle

Abstract: Background: Needle samples may not provide sufficient diagnostic material for the assessment of mediastinal lymph nodes. Objective: The study compared the specimen size and diagnostic performance of a new 19-G endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) needle to that of a standard 22-G EBUS-TBNA needle in a swine model of granulomatous lymphadenopathy. Methods: Granulomatous inflammation was induced in mediastinal lymph nodes (LNs) of 10 domestic swine by injection oftalc slur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In a preclinical evaluation comparing a novel 19-G flexible needle with a commercial 22-G EBUS-TBNA sampling needle, the samples collected with the 19-G needle were larger and had less blood contamination than those obtained with a 22-G needle (15). In our study, the use of the 19-G needle also provided sufficient tissue samples with less blood contamination that proved useful for diagnosing retinal hemangioblastoma, lung adenocarcinoma, and tuberculous lymphadenitis and for evaluating the PD-L1 expression in specimens whose findings had initially been negative with a 21- or 22-G needle.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical evaluation comparing a novel 19-G flexible needle with a commercial 22-G EBUS-TBNA sampling needle, the samples collected with the 19-G needle were larger and had less blood contamination than those obtained with a 22-G needle (15). In our study, the use of the 19-G needle also provided sufficient tissue samples with less blood contamination that proved useful for diagnosing retinal hemangioblastoma, lung adenocarcinoma, and tuberculous lymphadenitis and for evaluating the PD-L1 expression in specimens whose findings had initially been negative with a 21- or 22-G needle.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in needle development resulted in a flexible 19G (Flex 19 G) needle with an inner diameter of 0.69 mm. In a preclinical swine model of granulomatous lymphadenopathy, the Flex 19G and 22G EBUS-TBNA needles had a similar diagnostic yield, but the Flex 19G needle samples were larger [9].…”
Section: Introductionmentioning
confidence: 89%
“…In studies performed in general populations of subjects with mediastinal lymphadenopathy (not specifically sarcoidosis) undergoing EBUS-TBNA, it has been demonstrated that the use of either suction or the stylet provided with the EBUS-TBNA needle does not affect the diagnostic yield [16,29]. The use of a novel flexible 19G needle has also been investigated in preliminary studies [30,31]. Before the present study, there was no report on the effect of the number of revolutions performed inside the lymph node on the diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%